2022
DOI: 10.1093/ibd/izac039
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Effectiveness of a Generic Oral Nutritional Supplement With Specialized Formula in the Treatment of Active Pediatric Crohn’s Disease

Abstract: Background Exclusive enteral nutrition (EEN) is the recommended induction treatment of mild to moderate active pediatric Crohn’s disease (CD). This study compared outcomes of 2 proprietary polymeric formulas. Treatment effectiveness was examined along with practical aspects of formula delivery and differences in estimated treatment costs. Methods Data were retrospectively collected from patients with CD who received a generic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…, Several studies have recently been published which expanded our knowledge on the use of EEN in the management of paediatric CD (Table 1). In a retrospective study, there were no differences in clinical remission rates, improvement of anthropometry indices or inflammatory biomarkers between an CD specific enteral nutrition formula and a generic oral nutritional supplement [5].…”
Section: Exclusive Enteral Nutrition In the Management Of Paediatric ...mentioning
confidence: 89%
“…, Several studies have recently been published which expanded our knowledge on the use of EEN in the management of paediatric CD (Table 1). In a retrospective study, there were no differences in clinical remission rates, improvement of anthropometry indices or inflammatory biomarkers between an CD specific enteral nutrition formula and a generic oral nutritional supplement [5].…”
Section: Exclusive Enteral Nutrition In the Management Of Paediatric ...mentioning
confidence: 89%
“…The composition of formulas used as EEN varies greatly [ 30 ]. To date, no formula has shown any benefits over any other formula in inducing clinical remission in CD [ 31 , 32 ]. A compositional analysis on 61 formulas successfully used as EEN to induce remission in active CD, as compared to dietary intake of children with longstanding CD, revealed that formulas used as EEN generally contained lower sugar, total fat, saturated fat, and fiber content, and a higher percentage of protein [ 30 ].…”
Section: Exclusive Enteral Nutritionmentioning
confidence: 99%